Adaptation of the University Student Engagement Inventory (USEI) Scale for Students Taking Online Lectures - Nabila Triputri Aldelya; Farah Aulia (International Journal of Psychology and Health Science, 2026)
This study aims to adapt and test the validity and reliability of the University Student Engagement Inventory (USEI) measuring instrument by João Maroco (2016) into the context of Indonesian students who take online lectures. This measuring instrument consists of 15 statement items expressed into 3 dimensions, which are 5 emotional engagement items, 5 behavioral engagement items and 5 cognitive engagement items. The adaptation process was carried out through translation and adjustment to the cultural context and the Indonesian education system. The research subjects were 174 students who took online learning. The data were analyzed using descriptive statistics, reliability tests with Cronbach's Alpha analysis, and confirmatory factors (Confirmatory Factor Analysis/CFA). The results showed that the scale had fairly good internal reliability (α = 0.738). The three-factor CFA model showed very good balance (CFI = 0.984, TLI = 0.981, RMSEA = 0.0202). Three items were found to be statistically invalid and were removed from the final version of the scale. The final version of the Scale consists of 12 items described in three main dimensions and demonstrates adequate validity and reliability.